2022
DOI: 10.3390/en15072369
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Efficiency and Low-Carbon Optimization in Shanxi Province under “Dual Carbon” Background

Abstract: As an important energy base in China, Shanxi Province, in its economic development, has depended heavily on coal resources. However, enormous coal consumption produces a large amount of carbon dioxide and an aggravated ecological problem. In this paper, the super efficiency slack-based measure and data envelopment analysis (SBM-DEA) model and Malmquist index were used to calculate the energy consumption and carbon emission efficiency of 11 prefecture-level cities in Shanxi in the period from 2000 to 2020. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…As a result, policies such as mandatory carbon emissions, carbon taxes, carbon trading, and carbon offsets have emerged and become the main measures to control carbon dioxide emissions [3][4][5][6]. The purpose of a low-carbon emission policy is that the construction and development of the social and economic system can achieve low-carbon emissions [7][8]. Low carbon emissions can be defined in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, policies such as mandatory carbon emissions, carbon taxes, carbon trading, and carbon offsets have emerged and become the main measures to control carbon dioxide emissions [3][4][5][6]. The purpose of a low-carbon emission policy is that the construction and development of the social and economic system can achieve low-carbon emissions [7][8]. Low carbon emissions can be defined in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the DEA method only evaluates efficiency from a static perspective, scholars further introduced the Malmquist index to dynamically analyze the efficiency. In this circumstance, some scholars have used both the DEA method and the Malmquist index in their respective studies [16][17][18][19][20][21]. The proposed methods have been proven to be effective, therefore, this study selects the Malmquist index based on the SBM model to analyze the dynamic trends of the environmental efficiency of construction waste generation in China.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have found that technological innovation [ 5 , 6 , 7 ], industrial structure [ 8 , 9 , 10 ], human capital [ 11 ], FDI [ 3 , 12 ], and urban agglomeration [ 10 ], etc., are among the more important factors influencing TFCEE. At the same time, some scholars have also investigated the impact of policy instruments on TFCEE, such as the low carbon city policy [ 12 ], dual carbon policy [ 9 ], and environmental regulation [ 13 ]. However, few studies have examined the impact of VAT policy reform on total factor carbon emission efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, this paper is the first to use China’s VAT reform as a quasi-natural experiment to examine the impact of tax incentives on the total factor carbon emission efficiency at the city level. Previous studies have focused more on the impact of policies on environmental regulation on carbon emission efficiency [ 9 , 13 ], and fewer studies have examined the effect of VAT reform on total factor carbon emission efficiency. In addition, by examining the impact of tax incentives on urban TFCEE with VAT as an exogenous shock, we can overcome the endogeneity problem of the model and help policymakers to assess the real impact of VAT reform better.…”
Section: Introductionmentioning
confidence: 99%